2024
DOI: 10.1186/s13046-024-02967-3
|View full text |Cite
|
Sign up to set email alerts
|

PARD3 drives tumorigenesis through activating Sonic Hedgehog signalling in tumour-initiating cells in liver cancer

Junyu Wu,
Hor-Yue Tan,
Yau-Tuen Chan
et al.

Abstract: Background Par-3 Family Cell Polarity Regulator (PARD3) is a cellular protein essential for asymmetric cell division and polarized growth. This study aimed to study the role of PARD3 in hepatic tumorigenesis. Methods The essential role of PARD3 in mediating hepatic tumorigenesis was assessed in diet-induced spontaneous liver tumour and syngeneic tumour models. The mechanism of PARD3 was delineated by bulk and single-cell RNA sequencing. The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Overexpression of PARD3 maintained the self-renewal ability of the CD133 + TIC population within hepatocellular carcinoma (HCC) cells and promoted the in vitro and in vivo tumorigenicity of CD133 + TICs. Mechanistically, PARD3 interacted with aPKC to further activate SHH signalling and downstream stemness-related genes [ 15 ]. In the present investigation, the expression levels of PARD3 and DCAF1 were positively correlated in HCC tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of PARD3 maintained the self-renewal ability of the CD133 + TIC population within hepatocellular carcinoma (HCC) cells and promoted the in vitro and in vivo tumorigenicity of CD133 + TICs. Mechanistically, PARD3 interacted with aPKC to further activate SHH signalling and downstream stemness-related genes [ 15 ]. In the present investigation, the expression levels of PARD3 and DCAF1 were positively correlated in HCC tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PARD3 is reported to be dysregulated and to participate in the progression of several types of malignancies, high expression of PARD3 predicts poor prognosis in HCC [ 14 ]. And a recent study has found that PARD3 drives tumorigenesis through activating Sonic Hedgehog signalling in tumour-initiating cells in liver cancer [ 15 ]. Meanwhile, in CRC, PARD3 was found interacted with Trip6, promoted EMT and activated Akt signaling [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Hedgehog signaling pathway, known for its high conservation, plays a crucial role in regulating fundamental processes like cell proliferation, differentiation, migration, and adhesion [ 168 ]. Moreover, it has been closely linked with the development of liver cancer [ 169 ]. Cepharanthine (CH), a biscoclaurine alkaloid derived from the roots of Stephania cephalantha Hayata, exhibits promising anti-tumor activity against various cancer types.…”
Section: The Main Action Pathway and Potential Mechanism Of Natural C...mentioning
confidence: 99%